Pathways to Decarbonization in Indonesia: Mediating Effects of Renewable Energy and Energy Efficiency on the Economic Growth–Emission Nexus - Sinaga, Anton Atno Parluhutan (International Journal of Energy Economics and Policy, 2026)
The transition toward low-carbon development has emerged as a critical global agenda, especially for developing countries like Indonesia, which are heavily reliant on fossil fuels. This study investigates the mediating role of renewable energy and energy efficiency in the relationship between economic growth and carbon emissions in Indonesia from 2000 to 2023. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study finds that economic growth significantly increases carbon emissions, while both renewable energy and energy efficiency exert a negative impact on emissions. Moreover, these two variables partially mediate the growth–emissions nexus, with energy efficiency showing a stronger mitigation effect than renewable energy. The research also highlights that industrial energy efficiency yields greater emission reductions compared to the transport sector. Moderating effects of trade openness and institutional quality are found to enhance the effectiveness of energy policies. The study concludes that a combined strategy involving clean energy adoption, sectoral energy efficiency, and institutional reform is essential for achieving Indonesia’s low-carbon development goals. The findings contribute both theoretically and practically to the literature on decarbonization and sustainable energy transitions in emerging economies.